Sensitive, low cost and disposable electrochemical dopamine sensor based on Ag-NP/f-MWCNT/Poly (L-Cysteine)/ PGE - Arvas, Melih Besir; Kocyigit, Nilufer; Yazar, Sibel; Uzbicen, Kardelen; Yaylagul, Sultan; Yagci, Ozlem; Sahin, Musa (SPRINGER HEIDELBERG, 2025)
In this study, a single-step electrochemical method was employed to coat the electrode surface with a hybrid material comprising silver nanoparticles (AgNPs), functionalised multi-walled carbon nanotubes (f-MWCNTs) and poly(L-cysteine). This material was used for the electrochemical determination of dopamine (DA). The electrocatalytic effect of the AgNPs/f-MWCNT/Poly(L-cysteine) hybrid material in DA determination exhibited superior performance in the sensitive and selective determination of DA, due to its well-designed morphology and surface functional groups. The spectroscopic, structural and morphological analyses of the AgNPs/f-MWCNT/Poly(L-cysteine)/PGE sensor electrode were conducted using XRD, FT-IR, Raman and SEM-EDS. The electrochemical properties and sensitivity of the sensor electrode employed in the determination of DA were investigated through the utilisation of cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and differential pulse voltammetry (DPV) methodologies. The limit of detection (LOD) value of the DA sensor was calculated to be 0.068 mu M, while the limit of quantification (LOQ) value was determined to be 0.23 mu M. Furthermore, linear ranges of 0.1 mu M to 5.0 mu M and 10 mu M to 1000 mu M were obtained. The repeatability test of the sensor electrode was also performed, and the RSD value was found to be 4.14%.
Keywords: Electrochemical sensor; Dopamine; Silver nanoparticles; f-MWCNT; Polyaminoacids; NANOPARTICLES; NANOCOMPOSITES; ELECTRODE; GRAPHITE; Materials Science; Physics